HUBUNGAN TERPAAN PROMOSI PENJUALAN PADA AKUN INSTAGRAM @CIRCLEANDCOFFEE DAN CITRA MEREK DENGAN MINAT BELI PRODUK DI CIRCLE AND COFFEE - Kurniandy, Yody; Bayu Widagdo, Muhammad; Surayya Ulfa, Nurist (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This study investigates the relationship between sales promotion exposure and brand image perception through the Instagram account @circleandcoffee with purchase intention at Circle and Coffee. Circle and Coffee employs various marketing strategies including sales promotions and branding content to attract customer interest. However, their sales results exhibit fluctuations. This research aims to examine whether exposure to sales promotions and brand image perception positively correlate with product purchase intention. The research methodology employs correlation analysis to link data on sales promotion exposure, brand image perception, and purchase intention. The analysis reveals that exposure to sales promotions through the @circleandcoffee Instagram account has a significant positive relationship with product purchase intention at Circle and Coffee. Additionally, positive perceptions of the Circle and Coffee brand formed through this account also correlate positively with purchase intention. These findings suggest that marketing efforts focused on increasing sales promotion exposure and enhancing brand image through social media platforms can positively impact consumer purchase interest. The practical implications highlight the importance of relevant and engaging content in sales promotions, as well as cultivating a positive brand image to enhance Circle and Coffee sales performance.